2014
DOI: 10.1007/s11837-014-0938-7
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Analysis of Linear Friction-Welded 718 Plus Superalloy

Abstract: Access and use of this website and the material on it are subject to the Terms and Conditions set forth at NRC Publications Record / Notice d'Archives des publications de CNRC:http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?action=rtdoc&an=21272632&lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?action=rtdoc&an=21272632&lang=fr READ THESE TERMS AND CONDITIONS CAREFULLY BEFORE USING THIS WEBSITE.http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en Vous avez des questions? Nous pouv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Qian and Lippold [21] related intergranular HAZ liquation cracking to the combined effects of δ phase dissolution, boron carbide constitutional liquation, and grain boundary segregation. On the other hand, Zhang and Ojo [22,23] reported that the δ phase could actually constitutionally liquate in the HAZ during welding above their solvus (about 1010 • C in IN718) and enrich the grain boundary with Nb. Thrappel et al [24] and Muralidharan et al [25] reported that during rapid heating, second phase eutectic grain boundary precipitates such as γ/Laves or γ/NbC (at 1200 • C) present in the HAZ of wrought IN718 melted due to the lack of time for dissolution into the matrix.…”
Section: Of 20mentioning
confidence: 99%
“…Qian and Lippold [21] related intergranular HAZ liquation cracking to the combined effects of δ phase dissolution, boron carbide constitutional liquation, and grain boundary segregation. On the other hand, Zhang and Ojo [22,23] reported that the δ phase could actually constitutionally liquate in the HAZ during welding above their solvus (about 1010 • C in IN718) and enrich the grain boundary with Nb. Thrappel et al [24] and Muralidharan et al [25] reported that during rapid heating, second phase eutectic grain boundary precipitates such as γ/Laves or γ/NbC (at 1200 • C) present in the HAZ of wrought IN718 melted due to the lack of time for dissolution into the matrix.…”
Section: Of 20mentioning
confidence: 99%
“…[4][5][6][7] Friction welding technology does not require filler metal addition or protective gas shielding for joining similar and dissimilar materials. 2,[8][9][10] LFW process offers multiple advantages over other mechanical joining techniques, for example, fusion welding, 8,[11][12][13] as it can effectively avoid the welding defects like hot cracking and it has a lower possibility for the occurrence of dissolution of hardening precipitates 9,10,14 for precipitation-hardened alloys. Metals and thermoplastics have been joined in multiple variations, particularly non-axisymmetric configurations, using LFW in aerospace and automotive industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…Information on ATI 718Plus® is more limited. However, it seems likely that both large grain size [48] and high B and P levels in a modified ATI 718Plus® alloy have an impact on weld cracking [32]. The same study also indicated that cracking in Waspaloy was due to the extensive precipitation of inter-and intragranular y'.…”
Section: The Grain Structurementioning
confidence: 98%
“…The chemical composition in general and the presence of Nb and C in particular is important in this context [8,19,28]. However, it has been concluded that a eutectic liquid is not always detrimental for the hot cracking since in some cases it has been shown to heal cracks by backfilling [29][30][31][32]. Some researchers have monitored the grain structure of the weld deposit through variation of the weld process parameters in order to optimize the weldability.…”
Section: The Grain Structurementioning
confidence: 99%